Effects of Ion Exchange on the Mechanical Properties of Basaltic Glass Fibers. (19th May 2015) - Kuzmin, Konstantin L.; Zhukovskaya, Evgeniya S.; Gutnikov, Sergey I.; Pavlov, Yuriy V.; Lazoryak, Bogdan I.
Abstract : Basaltic glass fibers with different lithium oxide (6–14 mol%) and sodium oxide (2–14 mol%) contents were prepared. The influence of Li2 O and Na2 O content on the process of fiber manufacturing was investigated. Addition of alkali oxides reduced the forming temperature and substantially expanded the fiber‐forming temperature ranges. The obtained thermal data from differential thermal analysis revealed a decline in glass transition temperature ( T g ) of fibers against the compositional changes. The inclusion of Li2 O and Na2 O in the glass network led to a reduction in its thermal stability. The obtained X‐ray diffraction patterns and IR spectra of Li‐rich and Na‐rich basaltic glass fibers confirmed the formation of highly polymerized structures such as LiAl(Si2 O6 ) and (Na, K)(AlSiO4 ), respectively, and relatively depolymerized silicate anions. The effects of potassium–lithium and potassium–sodium ion exchange on the mechanical properties of basaltic glass fibers were investigated. As‐received Li‐rich and Na‐rich basaltic glass fibers were ion‐exchanged in potassium nitrate for different exchange times, and their mechanical properties were measured before and after chemical tempering. The measured tensile strength and Young's modulus values of the fibers showed an increase after treatment in molten salt.